Cybersecurity leadership demystified : a comprehensive guide to becoming a world-class modern cybersecurity leader and global CISO - Ozkaya, Erdal; Abdulhayoglu, Melih (Packt Publishing, 2022)
Gain useful insights into cybersecurity leadership in a modern-day organization with the help of use cases About This Audiobook Discover tips and expert advice from the leading CISO and author of many cybersecurity books Become well-versed with a CISO's day-to-day responsibilities and learn how to perform them with ease Understand real-world challenges faced by a CISO and find out the best way to solve them In Detail The chief information security officer (CISO) is responsible for an organization's information and data security. The CISO's role is challenging as it demands a solid technical foundation as well as effective communication skills. This audiobook is for busy cybersecurity leaders and executives looking to gain deep insights into the domains important for becoming a competent cybersecurity leader. The audiobook begins by introducing you to the CISO's role, where you'll learn key definitions, explore the responsibilities involved, and understand how you can become an efficient CISO. You'll then be taken through end-to-end security operations and compliance standards to help you get to grips with the security landscape. In order to be a good leader, you'll need a good team. This book guides you in building your dream team by familiarizing you with HR management, documentation, and stakeholder onboarding. Despite taking all that care, you might still fall prey to cyber attacks; this audiobook will show you how to quickly respond to an incident to help your organization minimize losses, decrease vulnerabilities, and rebuild services and processes. Finally, you'll explore other key CISO skills that'll help you communicate at both senior and operational levels. By the end of this audiobook, you'll have gained a complete understanding of the CISO's role and be ready to advance your career. Audience This audiobook is for aspiring as well as existing CISOs. This audiobook will also help cybersecurity leaders and security professionals understand leadership in this domain and motivate them to become leaders. A clear understanding of cybersecurity posture and a few years of experience as a cybersecurity professional will help you to get the most out of this audiobook.